Parental Behaviors and Beliefs, Child Temperament, and Attachment Disorganization. Issue 2 (April 2015) - Wang, Feihong; Cox, Martha J.; Mills‐Koonce, Roger; Snyder, Patricia
Abstract : This research examined alternative mechanisms in the etiology of attachment disorganization. The authors hypothesized that negative intrusive parenting would significantly predict children's attachment disorganization at age 12 months within a diverse community sample. Of more substantial interest, the authors tested moderational mechanisms in the association between negative intrusive parenting, parental strong belief in discipline and control, child difficult temperament, and children's attachment disorganization. Using a multiple regression analytic approach, this research found that negative intrusive parenting significantly predicted children's attachment disorganization. This prediction was more significantly related to children's levels of attachment disorganization when it was paired with stronger rather than weaker parental beliefs in discipline and control. In contrast, when children had difficult temperament at 6 months, it was only when parents held very weak beliefs in discipline and control that children were at higher risk for attachment disorganization. Implications of the findings were discussed accordingly.